Individual load-velocity measures are associated with 2,000-m rowing ergometer performance in German national rowers - Jacobs, M. W.; Schumann, M. (Frontiers in Sports and Active Living, 2025)
Objective: Neuromuscular abilities were previously linked to 2,000 m rowing performance (TT) but the relationship with load-velocity profiles [LVP; e.g., peak power (PP) and power at different relative loads] remains unclear. This cross-sectional study assessed the associations between these parameters and TT and different race splits in well-trained rowers.